Deformation of Copahue volcano: Inversion of InSAR data using a genetic algorithm - Velez, Maria Laura; Euillades, Pablo; Caselli, Alberto; Blanco, Mauro; Díaz, Jose Martínez (Journal of volcanology and geothermal research, 2011)
The Copahue volcano is one of the most active volcanoes in Argentina with eruptions having been reported as recently as 1992, 1995 and 2000. A deformation analysis using the Differential Synthetic Aperture Radar technique (DInSAR) was performed on Copahue–Caviahue Volcanic Complex (CCVC) from Envisat radar images between 2002 and 2007. A deformation rate of approximately 2 cm/yr was calculated, located mostly on the north-eastern flank of Copahue volcano, and assumed to be constant during the period of the interferograms. The geometry of the source responsible for the deformation was evaluated from an inversion of the mean velocity deformation measurements using two different models based on pressure sources embedded in an elastic homogeneous half-space. A genetic algorithm was applied as an optimization tool to find the best fit source. Results from inverse modelling indicate that a source located beneath the volcano edifice at a mean depth of 4 km is producing a volume change of approximately 0.0015 km/yr. This source was analysed considering the available studies of the area, and a conceptual model of the volcanic–hydrothermal system was designed. The source of deformation is related to a depressurisation of the system that results from the release of magmatic fluids across the boundary between the brittle and plastic domains. These leakages are considered to be responsible for the weak phreatic eruptions recently registered at the Copahue volcano. ►We calculate ground deformation at Copahue volcano with DInSAR technique. ►Subsidence is observed in partial coincidence with the volcano edifice. ►Two analytical models are tested using optimised inversion using a genetic algorithm. ►An ellipsoidal oblate source seems to better fit the deformation data. ►A conceptual model of the volcanic–hydrothermal system is proposed.